2020
DOI: 10.21203/rs.3.rs-21315/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining chain link sampling with a community-based participatory action study of people who smoke drugs in two cities in British Columbia, Canada

Abstract: Background: The smoking of illicit drugs presents a serious social and economic burden in Canada. People who smoke drugs (PWSD) are at an increased risk of contracting multiple infections through risky drug practices. Peer-led harm reduction activities, and the resulting social networks that form around them, can potentially minimize the dangers associated with the smoking illicit drugs.Goal: The goal of this study is to examine the influence of peer-led harm reduction initiatives on drug behaviour by comparin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While the characteristics of people who consume drugs through non-injection routes of consumption have been described [23][24][25][26], less is known about the subpopulation of people who access SCS for oral, intranasal, or inhaled drug use. Recent evidence from a supervised consumption service in Canada demonstrated that program participants were predominantly Indigenous, male, and between the ages of 20-39 [17].…”
Section: Introductionmentioning
confidence: 99%
“…While the characteristics of people who consume drugs through non-injection routes of consumption have been described [23][24][25][26], less is known about the subpopulation of people who access SCS for oral, intranasal, or inhaled drug use. Recent evidence from a supervised consumption service in Canada demonstrated that program participants were predominantly Indigenous, male, and between the ages of 20-39 [17].…”
Section: Introductionmentioning
confidence: 99%